EU Energy Diplomacy in Promoting EU Market Rules On Palm Oil Through The IEU-CEPA Cooperation Framework - Nujaiba, Sindiana Lauza; Firdausi, Fariz Dzifaz; Permatasari, Intan Putri; Tirto, Nur Kholis Danu; Seru, Rayzhando Nesta Putra (Department of International Relations Universitas Pertamina, 2023)
Sustainable energy development is an effort made by the European Union in response to climate change. One form of the EU's efforts in developing sustainable energy is by setting standards for energy and energy raw materials that enter the EU market, one of which is palm oil. The European Union has firmly demonstrated its commitment to setting sustainability standards in the EU market. This is shown by one of the discussions of EU energy diplomacy, namely promoting market rules in producer and transit countries. This research aims to analyze the EU's success in encouraging Indonesia to implement sustainability standards for palm oil. This discussion will be qualitatively discussed using smart power theory. This research shows that the European Union's energy diplomacy to encourage sustainability standards in Indonesia is carried out through formal energy negotiations through the IEU-CEPA cooperation framework, namely palm oil standardization. To support this step, the European Union sets hard power in the form of sanctions and soft power in the form of co-optatives to show its commitment to promoting applicable EU market rules.